Defining the Breakpoint Duration of Staphylococcus aureus Bacteremia Predictive of Poor Outcomes. (5th April 2019) - Minejima, Emi; Mai, Nikki; Bui, Nancy; Mert, Melissa; Mack, Wendy J; She, Rosemary C; Nieberg, Paul; Spellberg, Brad; Wong-Beringer, Annie
Abstract: Background: Persistent Staphylococcus aureus bacteremia (SAB) is defined based on varying duration in literature. The primary objective was to determine the risk of poor outcomes in relation to bacteremia duration. Methods: Multicenter, prospective, observational study of adult hospitalized patients with SAB. Medical records were reviewed for pertinent data. Patients were grouped by bacteremia duration: short (1–2 days), intermediate (3–6 days), and prolonged (≥7 days) and compared for risk factors and outcomes. Results: Of 884 patients, 63% had short, 28% intermediate, and 9% prolonged bacteremia. Overall mean age was 57 years, and 70% were male. The prolonged group had the highest proportion of methicillin-resistant SAB ( P < .0001). Choice of antibiotic therapy did not significantly affect bacteremia duration; however, time to source-control procedure was delayed in the prolonged and intermediate groups compared with the short group (3.5 vs 3 vs 1 day, P < .0001). Metastatic complications, length of stay, and 30-day mortality were progressively worse as bacteremia duration increased ( P < .0001). Every continued day of bacteremia was associated with a relative risk of death of 1.16 (95% confidence interval, 1.10–1.22; P < .0001), with a significant increase in risk starting at 3 days as determined by receiver operating characteristic analysis. Conclusions: Optimal management of SAB should target bacterial clearance as soon as possible to minimize incremental risk of mortality with each day of positive blood culture. Delay in source control but not type of antistaphylococcal therapy was significantly associated with prolonged bacteremia and worse outcomes. Abstract : Every continued day of persistent Staphylococcus aureus bacteremia is associated with a 16% increased risk of death. Bacteremia duration of 3 days was found to best distinguish patients who died versus those who survived.